Pengembangan Sistem Informasi Perpustakaan pada SMP Plus Al-Kautsar Malang - Andhini Apsari Putri; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The library is a facility provided by SMP Plus Al-Kautsar to support the teaching and learning process. One of the services provided at this library is circulation services. However, in the implementation of these services, there are several obstacle, including difficulities in managing and finding data which results in the work of officers being less efficient. In addition, there are also obstacles to obtaining collection information and the availability of books in the library. Based on these problems, this study aims to build library information system that can assist the data management process and improve the efficiency of circulation services. The development model that used in this study is the waterfall model which includes the stage of requirement analysis and definition, system design, implementation and system testing. The requirements analysis phase produces 42 functional requirements and 1 non-functional requirement. System design produces documentation of object modeling and object interaction in UML notation, database design, algorithms, and user interfaces. The implementation phase produces an information system that is built by applying the model-view-controller pattern. Testing is conducted using validation testing and compatibility testing to determine that the system is running according to user needs and is able to run in various browser applications. Validation test results show valid values in 13 test cases. While the compatibility test results show that there is 1 major issue and 3 minor issues caused by some browser applications not supporting the CSS properties used.